Traffic monitoring and analysis Third international workshop, TMA 2011, Vienna, Austria, April 27, 2011. Proceedings - Domingo-Pascual, Jordi; Shavitt, Yuval; Uhlig, Steve (Lecture Notes in Computer Science, 2011)
This book constitutes the proceedings of the Third International Workshop on Traffic Monitoring and Analysis, TMA 2011, held in Vienna, Austria, on April 27, 2011 - co-located with EW 2011, the 17th European Wireless Conference. The workshop is an initiative from the COST Action IC0703 "Data Traffic Monitoring and Analysis: Theory, Techniques, Tools and Applications for the Future Networks". The 10 revised full papers and 6 poster papers presented together with 4 short papers were carefully reviewed and selected from 29 submissions. The papers are organized in topical sections on traffic analysis, applications and privacy, traffic classification, and a poster session.